2017
DOI: 10.1108/aaouj-01-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing students online learning behavior in blended courses using Moodle

Abstract: For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 22 publications
1
35
1
1
Order By: Relevance
“…In other words, the key challenge is to find the relevant dynamic characteristics of an individual student for a specific prediction task which would later help properly adapting the learning object for them [13]. Among the most important dynamic characteristics of students in a course are their learning behavior or preferences with regard to accessing learning resources, engaging with peers, and taking assessment tests [14]. Multiple research has concluded that students' activity data logged in different LMSs (like Moodle) could be used to represent their learning behavior in online courses (e.g., [14,15]).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the key challenge is to find the relevant dynamic characteristics of an individual student for a specific prediction task which would later help properly adapting the learning object for them [13]. Among the most important dynamic characteristics of students in a course are their learning behavior or preferences with regard to accessing learning resources, engaging with peers, and taking assessment tests [14]. Multiple research has concluded that students' activity data logged in different LMSs (like Moodle) could be used to represent their learning behavior in online courses (e.g., [14,15]).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, although the Moodle system provides some reporting tools, it does not provide specific features which can enable educators to directly monitor and evaluate the activities of students in relation to the structure and contents of the course and how it affects the learning process (Zorrilla, Millan, & Menasalvas, 2005). Based on experience, this keeps instructors from making meaningful sense and use of this data (Estacio & Raga, 2017 This paper describes a pilot study that discusses and illustrates the use of a novel approach in analyzing the log data generated by Moodle in a blended learning context. The proposed technique can be used to process and break down the multidimensional log data collected by the LMS in order to generate graphical representations that provide a profile of students' activities online, both individually and within a group.…”
Section: Introductionmentioning
confidence: 99%
“…Its quantification is not required in terms of the research question. Constructing separate models for each type of interactions accounts for students' preferences towards different participation forms and learning styles (Estacio and Raga Jr, 2017) and multiple viewpoints in the behavior analysis (Dobashi, 2017).…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Following broadly validated recommendations (Hernández García et al, 2017, Gašević et al, 2016, Davies and Graff, 2005, Estacio and Raga Jr, 2017, we operate with interactions' frequency instead of their duration. The argumentation behind is the absence of information in the latter upon the fact that the agent actually performed the activity within the registered time, which becomes especially problematic when the resources are available for download.…”
Section: Conceptual Framework and Measurement Of Variablesmentioning
confidence: 99%